2008
DOI: 10.1016/j.bbmt.2008.06.002
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Procedure for Hematopoietic Stem Cell Amplification Using a Serum-Free, Feeder Cell-Free Culture System

Abstract: Umbilical cord blood (UCB) is increasingly being used as a donor source of hematopoietic stem cells (HSCs) to treat blood malignancies. The main limitation to the widespread use of UCB is the low number of HSCs per unit. To compensate, a strategy of in vitro stem cell amplification has been attempted in different research laboratories. The major hurdle blocking success is the creation of culture conditions that support the growth of hematopoietic stem cells without their differentiation. We have designed a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…TNCs, Lin- or Lin+ cells from human umbilical cord blood or human bone marrow were used for our xenograft studies. NOD/SCID mice were prepared and transplanted as per standard protocols [11], [24], [25]. Our standard engraftment time of 8–10 weeks was used in the preliminary set of results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TNCs, Lin- or Lin+ cells from human umbilical cord blood or human bone marrow were used for our xenograft studies. NOD/SCID mice were prepared and transplanted as per standard protocols [11], [24], [25]. Our standard engraftment time of 8–10 weeks was used in the preliminary set of results.…”
Section: Resultsmentioning
confidence: 99%
“…The use of human cells allowed us to distinguish between human cells (HLA:ABC+) and mouse cells (H2Kd+). Hybrid cells would be positive for both human and mouse antigens [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it frequently happens that the UCB nucleated cell dose does not reach the lower acceptable limit for an adult, though making it suitable for most of pediatric patients [9]. Several approaches have been proposed to cope with this inconvenience, viz infusion of units from multiple donors [10][11][12], ex vivo or in vitro cell culturing prior to transplantation [13][14][15][16][17][18][19], non-myeloablative conditioning regimens [20], intra-bone inoculation [21].…”
Section: Introductionmentioning
confidence: 99%
“…MSC are defined by the presence of a number of surface antigens and a recent study suggests that these cell arise in the neural crest [22]. In addition it has been demonstrated that there is a lineage negative CD45+ cell population in cord blood which may also have multi-potential capabilities [27].…”
Section: The Development Of Regenerative Medicinementioning
confidence: 99%